A digital game‐based assessment of middle‐school and college students' choices to seek critical feedback and to revise. (29th April 2019) - Cutumisu, Maria; Chin, Doris B.; Schwartz, Daniel L.
Abstract: A major goal of contemporary education is to teach students how to learn on their own. Assessments have largely lagged behind this goal, because they measure what students have learned and not necessarily their learning processes. This research presents Posterlet, an assessment that collects evidence regarding the strategies that students choose while learning on their own. Posterlet is an educational game‐based assessment that measures two design thinking choices: students' choices to seek critical (ie, negative) feedback and to revise their work while they learn graphic design principles through creating posters. This research also presents an examination of students' choices to seek feedback and to revise, as well as of students' learning outcomes based on these choices. This game‐based assessment approach is empirically validated with three research studies sampling nearly 300 middle‐school and college students who played Posterlet and completed a posttest. Results show that the game helps students learn, as students who play the game before completing the posttest learn more graphic design principles than students who only complete the posttest. Moreover, the choices to seek critical feedback and to revise can predict learning and can be used as valid outcome measures for learning. Findings can be used in developing and evaluating models of instruction and assessment that may help students make informed learning choices. A discussion of present and future trends in theory regarding digital feedback environments is also included.